How an improved knowledge and information system can support productivity and livelihoods in the smallholder dairy sector. - Hooton, N.; Nyangaga, J.; Kinyanjui, H.; Agili, Grace (International Livestock Research Institute, 2004)
The Smallholder Dairy Project (SDP) carried out a short study into the knowledge and information systems of Kenya’s smallholder dairy sector. The rationale was that by understanding and catalyzing reform of this system, SDP would not only enhance the impact of its own research outputs, but would lead to a long-lasting improvement in the impacts of research and other information relevant to the sub-sector. The RAAKS (Rapid Appraisal of Agricultural Knowledge Systems) approach was used, involving a range of participatory approaches through workshops and semi-structured interviews, at national and local level. Key findings included poor co-ordination between the many public, private and NGO actors in the knowledge system, and problems in the regulation of privately provided information that limited farmers’ ability to access information to improve productivity. Options to improve the system and the linkages were explored through key informant workshops.